2008
DOI: 10.1007/s00128-008-9504-8
|View full text |Cite
|
Sign up to set email alerts
|

Decrease of 4,5,6,7-Tetrachlorophthalide in Paddy Field Soil After Aerial Application

Abstract: Variation in the fungicide, 4,5,6,7-tetrachlorophthalide (phthalide), in paddy field soil was investigated in order to evaluate its decrease after aerial application by a radio-controlled helicopter. The maximum concentrations of phthalide were 309-320 microg/kg dry, which were 83%-96% of the applied phthalide. The organic carbon normalized soil sorption coefficient (K(oc)) was calculated to be 94-96 mL/g at 1 h after the application. The calculated K(oc) values increased to 620-1,300 mL/g from 1 through 9 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Qin et al (2004) reported that the halflife of a nematicide, fosthiazate, was correlated with the organic matter content and clay content of soil. In contrast, the half-life of phthalide in the paddy soil with the higher organic content was shorter than that in the paddy soil with lower organic content (Iwashita et al 2008). The t 1/2 S values of bromobutide (21 days in paddy soil 1, 15 days in paddy soil 2) with organic contents of 7.21 % ± 1.34 % and 7.90 % ± 2.03 %, respectively, were larger than those (12 days) with contents of 4.31 % ± 0.86 % in paddy soil 3; the t 1/2 S values in paddy soils 1 and 2 with silt and clay contents of 36.5 % and 44.8 %, respectively, were larger than that with the content of 12.9 % in paddy soil 3.…”
Section: Resultsmentioning
confidence: 63%
See 4 more Smart Citations
“…Qin et al (2004) reported that the halflife of a nematicide, fosthiazate, was correlated with the organic matter content and clay content of soil. In contrast, the half-life of phthalide in the paddy soil with the higher organic content was shorter than that in the paddy soil with lower organic content (Iwashita et al 2008). The t 1/2 S values of bromobutide (21 days in paddy soil 1, 15 days in paddy soil 2) with organic contents of 7.21 % ± 1.34 % and 7.90 % ± 2.03 %, respectively, were larger than those (12 days) with contents of 4.31 % ± 0.86 % in paddy soil 3; the t 1/2 S values in paddy soils 1 and 2 with silt and clay contents of 36.5 % and 44.8 %, respectively, were larger than that with the content of 12.9 % in paddy soil 3.…”
Section: Resultsmentioning
confidence: 63%
“…The amounts reached maximum levels (about 20 % of the applied amounts) at 3 and 4 days after application, respectively (Amano et al 2001). We previously investigated variations in the concentrations of a fungicide, phthalide, in two paddy field soils at 137 days after application (Iwashita et al 2008). Phthalide was detected at maximum levels within 24 h after application, and was observed for 112 days after application in both paddy fields.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations